Ratik Basa Ritual Tulak Bala Di Nagari Singgalang X Koto Kabupaten Tanah Datar - Sabri Darmawan; Firdaus Firdaus; Muhammad Zulfahmi (Jurnal Musik Nusantara, 2023)
The research entitled Ratik Basa as a Tulak Bala Ritual in Nagari Singgalang, X Koto District, Tanah Datar Regency, aims to describe the series of implementation of "Ratik Basa in the Tulak Bala ritual and the views of the people who adhere to the Syattariah sect in Nagari Singgalang, X Koto District, Tanah Datar Regency" . Ratik Basa is a worship service that is integrated into religious traditions in the form of reciting dhikr in various contexts in the lives of the people of Nagari Singgalang. The research uses qualitative methods, field data collection techniques, literature study, observation, interviews and documentation using ritual theory, religious theory and perception theory. The results of the research show that the implementation of the Ratik Basa tradition is sung using a monophonic vocal technique, namely sung in one type of voice. For the people who adhere to the Syattariah sect in Nagari Singgalang, X Koto District, Tanah Datar Regency, Ratik Basa as a Tulak Bala Ritual ceremony is very essential. Because it is closely related to people's lives, especially the threat to the safety of nagari children in various forms of disaster, including natural disasters, dangerous disease attacks, famine, and others. Ratik Basa as a Tulak Bala Ritual is very important for people's lives because apart from being able to avoid all disasters, it has a positive value as an identity for Nagari Singgalang, and as a ritual means to foster ties of brotherhood between groups of adherents of the Syattariah sect and society in general.